PENERAPAN LEAN HOSPITAL DALAM MENINGKATKAN PELAYANAN GAWAT DARURAT DI RUMAH SAKIT: LITERATURE REVIEW - Aisyah Putri Amanda; Hasbi Miftah Faridz, Melda Julianti Kiswanto, Acim Heri Iswanto (CV. Adiba Aisha Amira, 2024)
Optimal service at the Emergency Department (ED) is crucial considering that every action must be effective and efficient in line with the philosophy of